Novel heterozygous TREX1 mutation in a juvenile systemic lupus erythematosus patient with severe cutaneous involvement treated successfully with Jak-inhibitors: a case report - Rossano, Martina; Conti, Emilio Amleto; Bocca, Paola; Volpi, Stefano; Mastrangelo, Antonio; Cavalli, Riccardo; Gattorno, Marco; Minoia, Francesca; Filocamo, Giovanni (Frontiers in Immunology, 2023)
Juvenile systemic lupus erythematosus (jSLE) is a complex inflammatory autoimmune disorder. In the last decades genetic factors and activation pathways have been increasingly studied to better understand their potential pathogenetic role. Genetic and transcriptional abnormalities directly involved in the type I interferons (IFNs) signaling cascade have been identified through family-based and genome-wide association studies. IFNs trigger a signaling pathways that initiates gene transcription of IFN stimulated genes, through the activation of JAK1, TYK2, STAT1 and STAT2. Thus, the use of therapies that target IFN pathway would represent a formidable advance in SLE. It is well known that JAK inhibitors have real potential for the treatment of rheumatic diseases, but their efficacy in the treatment of SLE remains to be elucidated. We report the case of a fourteen years old girl affected by jSLE, carrying a novel heterozygous missense variant on Three prime Repair EXonuclease 1 (TREX1), successfully treated with baricitinib on top of mofetil mycophenolate. TREX1 gene plays an important role in DNA damageCodice campo modificato This is a provisional file, not the final typeset article repair and its mutations have been associated with an overproduction of type 1 interferon. This report underlines the role of translational research in identifying potential pathogenetic pathways in rare diseases to optimize treatment.